Acute blood pressure behavior in hypertensive elderly people after a strength training session under the superserie method: Study protocol for a randomized clinical trial - Gonçalves Costa, Wanderson; Martins Cunha, Raphael (Manual Therapy, Posturology & Rehabilitation Journal, 2024)
Background: Chronic degenerative diseases have increased significantly, among them, systemic arterial hypertension (AH) stands out. The treatment of hypertension includes, in addition to specific hypotensive drugs, regular physical exercise. However, even though it is strongly recommended in national and international guidelines, the acute and subacute effects of physical exercise on the regulation mechanisms of the blood pressure system in different types of exercises still require further studies, especially regarding strength training and its methods in elderly people, which at least to our knowledge, there are not many studies published to date on this topic. Strength training has metabolic characteristics related to moderate intensity, a safe factor when it is related to the elderly, and can be an important ally for controlling the blood pressure system in this group. Objective: To evaluate the effects of a strength training session on blood pressure behavior in elderly people with hypertension. Methods: This is a randomized crossover clinical trial protocol. The minimum sample size was determined based on a previous study published by our research group. The size of 30 individuals was estimated, using a significance level of 5%, power of 80%, and a difference of 5mmHg in systolic blood pressure, after being included in the study, they will undergo a battery of tests, in order to outline their physical-functional and metabolic profile, and will be allocated into two protocols: CP (control protocol) and EP (experimental protocol). Control session, without exercise, and the EP which consists of a strength training session, using a superserie method. The blood pressure will be measured before the protocols, immediately after (minute 0), and at minutes 15 , 30, 45 and 60 after. Individuals will perform the other protocol, featuring the crossover design. Expected results: It is expected that by carrying out this study, we will obtain the hypotensive effect as well as contribute to the understanding of the effects of strength training under the superserie method on blood pressure levels in elderly people with hypertension, and its real practical applicability.